Reversal of cerebral dominance for language and emotion in a corpus callosotomy patient. Issue 6 (June 1986) - Joseph, R
Abstract : A case study of a right-handed individual with epilepsy and brain dysfunction of early onset is described who was found, following callosotomy (sparing the rostrum of the callosum) to be left hemisphere "dominant" for processing and/or expressing emotional and somesthetic information, and right hemisphere "dominant" in regard to the expression and comprehension of language and linguistic stimuli. Hence, a significant reversal in functional representation, due presumably to an injury suffered early in life, was observed. Moreover, following callosotomy the patient demonstrated severe disconnection syndromes in regard to right hand usage, the recognition of emotion, and the production and comprehension of linguistically related information. The left cerebrum appeared to be almost completely without linguistic representation except in regard to emotional language. The possible mechanisms involved in functional sparing and reversed representation are briefly discussed, and the effects of partial disconnection on the expression of these capacities is presented.